Detection of angiotensin II with mach-zehnder interferometric immunosensor - Meow, Melissa Xin Hui (2017)
We have seen an increase in the number of uses for optical fibres and technology is now looking towards constructing biosensors with these fibres. Optical fibres, being minute, satisfy the requirements of upcoming sensors of being portable and easy to fabricate. In this report, we explore the possibilities of utilising an in-line Mach-Zehnder Interferometer design for the detection of angiotensin II (a marker of diabetic nephropathy). Methods discussed include the use of CNBr-activated Sepharose, angiotensin II antibodies and angiotensin II antigens. The report also investigates the optimisation of coating of CNBr-activated Sepharose onto an optical fibre sensor, and the results obtained from the sensing of angiotensin II.